Upaya Pengendalian Secara Ergonomi pada Keluhan Low Back Pain pada Perawat di Rumah Sakit - Nunik Sulistyaningtyas (Unit Publikasi Ilmiah Perkumpulan Intelektual Madani Indonesia, 2022)
Nurses are one of the hospital resources, which are quite large in number and have a very decisive role in the quality of hospital services. Nurses in carrying out their work use a lot of bending and twisting movements, especially around the lower back, lifting heavy objects and transferring patients are the biggest risk factors for low back pain. The purpose of writing this article is to determine ergonomic risk control efforts in cases of low back pain in nurses in hospitals. The method used in this paper is a literature study approach. The collected data is then analyzed carefully. The results of the analysis from these journals are that the nonergonomic position of the nurse can cause low back pain. Nurse activities that are often carried out and have a high risk of low back pain are lifting and moving patients (patient mobilization), stitching wounds and installing infusions.